Pendampingan Peningkatan Potensi Objek Retribusi Daerah Melalui IMB di Distrik Tanah Miring dan Semangga Kabupaten Merauke: Assistance to Increase the Potential of Regional Retribution Objects through IMB in Tanah Miring and Semangga Districts of Merauke Regency - Henry Soleman Raubaba; Muchlis Alahudin (Fakultas Peternakan Universitas Papua, 2020)
ABSTRACT Increasing the potential of regional retribution objects in the Merauke Regency is an effort of the regional government to increase regional budget revenues. Izin Mendirikan Bangunan (IMB) or the